Ethical Healthcare During Public Health Emergencies: A Focus on Non-COVID-19 Patients - Iong MT (Risk Management and Healthcare Policy)
Man Teng Iong Faculty of Law, University of Macau, Macao, People’s Republic of ChinaCorrespondence: Man Teng Iong, Faculty of Law (FLL), University of Macau, E32, Avenida da Universidade, Taipa, Macau, People’s Republic of China, Email mantengiong@um.edu.moAbstract: Governments worldwide have made significant efforts to combat the COVID-19 pandemic. Nonetheless, measures against the COVID-19 outbreak have raised concerns relating to the measures that can affect health and endanger the lives of patients not related to COVID-19 but needing emergency treatments. For instance, ambulances were sometimes unable to access restricted zones for patients in urgent situations, and emergency departments were closed or refused urgent cases due to healthcare policies during the pandemic. To prevent such issues in future public health emergencies, changes to existing pandemic prevention measures are necessary. This article, through narrative review, intends to find a better healthcare policy during pandemic to protect proportionally public health and simultaneously guarantee the health and lives of non-COVID-19 patients needing emergency care. For this purpose, it provides three suggestions: ensuring ambulance access to confined areas, strengthening emergency department capabilities, and finding a balance between pandemic control and respect for patient rights. These suggestions are paramount to safeguard public health while securing the health and living for those needing urgent medical care.Keywords: healthcare policy, pandemic, COVID-19, individual rights, public health